Penyuluhan Manajemen Hipotensi pada Pasien Lansia - Happy Nurhayati; Suyanto Suyanto (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2022)
Hypotension in the elderly is a common condition and requires special attention in health management. This community service program aims to improve patient understanding of hypotension management through education and practical training. The methods used include socialization, interactive counseling, and evaluation of patient understanding before and after education. The results showed an increase in patient understanding from 55% before education to 85% after education. In addition, there was a decrease in complaints of dizziness from 80% to 40% after the intervention. These findings indicate that health education plays an important role in increasing patient awareness and readiness in managing hypotension. This program is recommended to be implemented widely to improve the quality of life of elderly patients.